Performance, carcass, and meat traits of different cattle types - Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station, 2011)
Different crossbred (X) cattle types were evaluated for growth, feed efficiency, carcass and meat traits. Steers were studied from mating Angus (A), Hereford (H), Brahman (B), Sahiwal (S), Pinzgauer (P), and Tarentaise (T) sires to Angus and Hereford females.
Keywords: Beef; Performance; Carcass; Meat traits